Encyclopedia of Aerospace Engineering 2010
DOI: 10.1002/9780470686652.eae187
|View full text |Cite
|
Sign up to set email alerts
|

Guided Wave Methods for Structural Health Monitoring

Abstract: This article reviews the state of the art in guided wave (GW) methods for structural health monitoring (SHM). The GW methods permit on‐demand interrogation of the structure to determine its current state of structural health (“active SHM”). The enabling element for active SHM is the piezoelectric wafer active sensor (PWAS), which allows both transmission and reception of GW into the structure. The mechanisms of Lamb wave excitation and detection with PWAS transducers are first presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Guided waves (GW) are one of the most promising tools for structural health monitoring (SHM) of large plate-like structures and have attracted a great deal of interest from the research community [1,2]. GW-based techniques work on the principle that that the waves will be reflected by discontinuities in the medium (boundaries, damage).…”
Section: Introductionmentioning
confidence: 99%
“…Guided waves (GW) are one of the most promising tools for structural health monitoring (SHM) of large plate-like structures and have attracted a great deal of interest from the research community [1,2]. GW-based techniques work on the principle that that the waves will be reflected by discontinuities in the medium (boundaries, damage).…”
Section: Introductionmentioning
confidence: 99%
“…A typical pitch–catch active-sensing diagnostic approach for hotspot SHM is to compare the difference (also referred to as scatter signal) between the receiving acousto-ultrasonic signal, in the form of a properly defined DI, from an actuator before and after the initiation of crack growth aiming at the detection of damage and estimation of its size (damage quantification). 16 As mentioned, a recent study by Janapati et al 10 showed that the dominating factors that influence the DI from one coupon to another within a nominally identical population are the sensor and actuator locations as well as the crack orientation for the same crack size. The sensor–actuator locations are defined relative to the target hotspot area under inspection.…”
Section: Methods Of Approachmentioning
confidence: 98%
“…1–9 The advantages of implementing SHM methods include the potential for improved safety and reliability, enhanced performance aligned with the actual structural state and potentially constrained within properly selected operating envelopes, increased resilience and sustainability, reduced maintenance and life-cycle cost, and ultimately the real-time structural awareness and the transition to condition-based maintenance. 1,4,6 Although SHM methods have shown high potential in providing real-time capabilities in damage detection, localization, and quantification tasks for real-life structures, one of the major challenges, similar to many other types of sensor-based systems facing real-life deployment, is still the lack of “trust” on the sensing data. The diagnostic error originating from sensing data needs to be quantifiable and validated through either experimental or analytical methods for the applied SHM approach.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, structural health monitoring (SHM) methodologies based on guided ultrasonic waves has attracted a great deal of interest, as they permit covering relatively large areas with a small number of sensors [ 1 ]. Lamb wave methods are sensitive to small damage, e.g., fatigue cracks in metallic structures or disbands and delamination in composite structures [ 2 ].…”
Section: Introductionmentioning
confidence: 99%